Syndromy vaskulární komprese mozkových nervů a neurogenní hypertenze - Plas, J (Rozhledy v chirurgii, 2003)
The presented paper is a review of syndromes which till recently had an obscure cause and still have attributes such as "primary" or "essential". Their common denominator is vascular compression of the roots of the appropriate cephalic nerves. The syndromes include trigeminal neuralgia, glossopharyngeal neuralgia, hemifacial spasm, some forms of tinnitus and vertigo, exceptionally toricollis. Vascular compression of the ventrolateral oblongata on the left leads to neurogenic hypertension. The author discusses the state of knowledge on the aetiology of syndromes, the clinical and laboratory research of which contributed some findings on the physiology and pathophysiology of the mentioned conditions. At the same time the authors present their own experience with the therapeutic method of syndromes--microvascular decompression.
Keywords: Cerebrovascular Disorders; pseudotumor cerebri; Glossopharyngeal Nerve Diseases; nemoci kraniálních nervů; Cranial Nerve Diseases; neuralgie trigeminu; cerebrovaskulární poruchy; nemoci bloudivého nervu; Nerve Compression Syndromes; úžinové syndromy; Pseudotumor Cerebri; lidé; Vagus Nerve Diseases; hemifaciální spazmus; Hemifacial Spasm; Trigeminal Neuralgia; nemoci nervus glossopharyngeus; Humans